2017
DOI: 10.3389/fphys.2017.00481
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Plasma Kallikrein-Kinin System Proteins Performed by Heparan Sulfate Proteoglycans

Abstract: Human plasma kallikrein-kinin system proteins are related to inflammation through bradykinin. In the proximity of its target cells, high molecular weight kininogen (H-kininogen) is the substrate of plasma kallikrein, which releases bradykinin from H-kininogen. Heparan sulfate proteoglycans (HSPGs) play a critical role in either recruiting kinin precursors from the plasma, or in the assembly of kallikrein-kinin system components on the cell surface. Furthermore, HSPGs mediate the endocytosis and activation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
0
14
0
1
Order By: Relevance
“…In a previous study, it was found that TCE exposure resulted in kallikrein-kinin system (KKS) activation, including that of bradykinin (BK) and the bradykinin receptor (B1R/B2R). Human plasma KKS proteins are related to inflammatory responses and immune disease through BK (Motta and Tersariol 2017). BK is released from kininogen by kallikrein, and metabolized rapidly to Des-Arg-BK (DABK) by kininase (Sang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was found that TCE exposure resulted in kallikrein-kinin system (KKS) activation, including that of bradykinin (BK) and the bradykinin receptor (B1R/B2R). Human plasma KKS proteins are related to inflammatory responses and immune disease through BK (Motta and Tersariol 2017). BK is released from kininogen by kallikrein, and metabolized rapidly to Des-Arg-BK (DABK) by kininase (Sang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…FXI releases a large D5 fragment, Arg428‐Lys520 . Recently studied HK‐interacting proteases include: MASP‐1 and MASP‐2 (lectin pathway of complement activation), neutrophil elastase (increased in PE), FXII (increased in response to estrogen and implicated in recurrent pregnancy loss), tissue kallikrein, plasmin, and calpains . Human mast cell tryptase was shown to cleave multiple sites within the LC of HK .…”
Section: Discussionmentioning
confidence: 99%
“…Human mast cell tryptase was shown to cleave multiple sites within the LC of HK . Additionally, HK bound to ECs is internalized and fused to lysosomes, containing proteases such as cathepsins B and L …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations